Antifungal Bioassay‐Guided Fractionation of an Oil Extract of Propolis. Issue 5 (3rd September 2013) - Finger, Daiane; Machado, Christiane Schinieder; Torres, Yohandra Reyes; Quináia, Sueli Percio; Thomaz, Amanda Cristina Godot; Gobbo, Angélica Rita; Monteiro, Marta Chagas; Ferreira, Antonio Gilberto; Sawaya, Alexandra Christine Helena Frankland; Eberlin, Marcos Nogueira
Abstract The study aimed to evaluate the antifungal potential of an extract of propolis obtained with edible vegetable oil (ODEP) and to identify antifungal compounds in this extract. Propolis sample was extracted with canola oil. After filtration, the oily liquid extract was submitted to solvent partition and dried to obtain ODEP, which was tested in vitro against Candida albicans strains. ODEP was fractioned on Sephadex and by high‐performance liquid chromatography (HPLC). Active fractions and/or a pure compound were analyzed by nuclear magnetic resonance, liquid chromatographic mass spectrometry (LC–MS) and liquid chromatography‐tandem mass spectrometry (LC–MS/MS) to characterize their chemical composition. Bioassay‐guided fractionation allowed the isolation of dihydrokaempferide, which was also quantified in ODEP by HPLC together with the total flavonoid content. Kaempferide and isosakuranetin were identified by LC–MS and LC–MS/MS in fractions with a potential activity against C. albicans. In vitro assays showed that some fractions from ODEP produced better inhibition of C. albicans than the propolis extract itself. Practical Applications Aqueous or ethanolic extracts of propolis (EEP) are widely used in alternative homemade medicine products mainly because of their antimicrobial and healing properties. Edible vegetal oils are known to extract bioactive compounds from propolis. The resulting extract (ODEP) has several advantages over the common EEP, such as the possibility of new pharmaceutical presentations for topical or internal applications. Because of the absence of ethanol in its formulation, edible ODEP are expected to be more tolerated. In this study, ODEP was active in vitro against Candida albicans strains. This supports the use of ODEP as an alternative to EEP and also its potential for topical application in combination with antifungal drugs. In addition, the ingestion of ODEP (e.g., contained in gelatin capsules), which have a high percentage of flavonoids, could be of nutritional value, helping to reach the recommended daily amounts of flavonoids and phenolic compounds.